Evaluation of stormwater runoff quality during monsoon and inter-monsoon seasons at tropical urban catchments - Chow M.F.; Yusop Z.; Teo F.Y. (Taylor and Francis Ltd., 2023)
catchment; concentration (composition); monsoon; pollutant transport; rainfall; runoff; stormwater; tropical environment; urban area; water quality; Malaysia